2010
DOI: 10.1118/1.3512798
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the respiratory signals acquired by different respiratory monitoring systems used in respiratory gated radiotherapy

Abstract: The estimation of the position of the tumor centroid and tumor shape may vary with the use of different respiratory monitoring systems. This implies that it is preferable to use the same respiratory monitoring system with 4DCT, 4DPET-CT, and linac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…( 7 , 8 , 9 , 18 ) Our results for mean (SD) for amplitude, 1.0 (0.5) cm, and period, 3.7 (1.0) s, fall into the range of motion found for external motion range of amplitudes of 3 mm to 3 cm ( 8 , 9 ) and a range of period of 4.8 (1.2) s. ( 18 ) …”
Section: Discussionsupporting
confidence: 54%
“…( 7 , 8 , 9 , 18 ) Our results for mean (SD) for amplitude, 1.0 (0.5) cm, and period, 3.7 (1.0) s, fall into the range of motion found for external motion range of amplitudes of 3 mm to 3 cm ( 8 , 9 ) and a range of period of 4.8 (1.2) s. ( 18 ) …”
Section: Discussionsupporting
confidence: 54%
“…De Groote17 proposed a model showing that if there exists asynchrony between motions along the dorsoventral and lateral directions with respiration, there will be a phase shift between the anterior–posterior movement (as measured as the RPM signal) and the change in abdominal perimeter (as measured as the ANZAI belt signal). In addition, in previous studies comparing different external surrogates,13, 16, 18 shape distortion can be observed between the respiratory traces in patients, which has not been investigated in those studies.…”
Section: Introductionmentioning
confidence: 93%
“…Different synchronization tools are offered by manufacturers; the main tools include the Real Time Position Management™ system from Varian Medical Systems (Palo Alto, CA), the pressure sensor AZ-733V from Anzai Medical (Tokyo, Japan) 7 or a deformable belt proposed by Medspira IBC System (Minneapolis, MN).…”
Section: Introductionmentioning
confidence: 99%